MR-Guided Drug Release From Liposomes Triggered by Thermal and Mechanical Ultrasound-Induced Effects - Patrucco, Deyssy; Terreno, Enzo (Frontiers in Physics, 2020)
One of the most challenging tasks of the cancer research is the enhancement of the amount of the chemotherapeutic agent that can reach the target site. To achieve this goal, nanovectors capable of encapsulating the drug and releasing it following a specific stimulus have been developed. In light of this, a key point is the necessity to monitor the effective drug release through a safe and highly performing imaging technology such as Magnetic Resonance Imaging (MRI). Liposomes are highly biocompatible nanovesicles that consist of bilayered phospholipid-based membrane encompassing an aqueous core. Almost 20 drug-loaded liposomes are currently approved for clinical use in USA and EU countries. If a liposomal nanomedicine is loaded with an MRI agent whose contrast is sensitive to the microenvironment and with a release kinetics similar to the co-transported drug, the system can act as an imaging reporter of drug release. This Perspective will offer a critical and brief overview of using MRI not only to verify and monitor the release process but also as a valuable tool to predict the therapeutic outcome. In particular, it will be presented representatives preclinical studies illustrating the in vivo potential of MRI-guided drug release protocols triggered by thermal and mechanical ultrasound-induced effects. Considering the therapeutic advantages of this approach, the possible benefits in reducing the side effects and the good results reported at preclinical level, there is a reasonable hope that the near future could witness the entrance in clinical routine of MRI-guided procedures supporting ultrasound-induced drug release protocols.